Review of the genus Keilbachia Mohrig (Diptera: Sciaridae), with the description of eleven new species - Vilkamaa, Pekka; Menzel, Frank; Hippa, Heikki (Zootaxa, 2009)
Collection materials for specimens of the genus Keilbachia Mohrig, 1987 (Sciaridae) were studied. The following new species are described and figured: Keilbachia acumina sp. n. (Japan), K. adjuncta sp. n. (Taiwan), K. bifida sp. n. (Nepal), K. brevicoxa sp. n. (India), K. camptospina sp. n. (Vietnam), K. cornuta sp. n. (Japan), K. criniloba sp. n. (India), K. inscissa sp. n. (Nepal), K. macripes sp. n. (Nepal), K. megacantha sp. n. (Japan), and K. trispinoides sp. n. (India). Additionally, Sciara neglecta Johannsen, 1912, is combined in the genus Keilbachia Mohrig. New faunistic records are presented for the species Keilbachia ferrata (Japan, Finland, Sweden), K. neglecta (USA), K. praedicata (Taiwan) and K. sasakawai (Japan). All 52 species, currently included in Keilbachia, are listed, and a complete literature synopsis on the genus is provided.